2019
DOI: 10.1155/2019/2917124
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Sialic Acid and IL10 Levels in Stage 1 and 2 Periodontitis Patients

Abstract: Objective The role of biomarkers in staging and grading periodontal disease has become detrimental in relation to the overall treatment plan. This study aimed at evaluating and comparing the role of sialic acid and IL10 in the early and moderate stages of periodontitis. Materials and Methods Patients were selected according to the assessment of pocket depth and radiographic bone loss. Bone loss was calculated as <15% for stage 1 and 15–33% for stage 2. Salivary samples were collected using spit technique 2 hrs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
1
6
1
Order By: Relevance
“…It has the capacity to inhibit cytokine synthesis by T cells which may deploy a strong regulatory effect on immune responses in periodontal disease. It is less seen or absent in severe periodontitis [ 54 , 55 ], which corroborate with our results. Many studies reported the positive role of IL-10 in preventing periodontitis progression and promoting its stability.…”
Section: Discussionsupporting
confidence: 92%
“…It has the capacity to inhibit cytokine synthesis by T cells which may deploy a strong regulatory effect on immune responses in periodontal disease. It is less seen or absent in severe periodontitis [ 54 , 55 ], which corroborate with our results. Many studies reported the positive role of IL-10 in preventing periodontitis progression and promoting its stability.…”
Section: Discussionsupporting
confidence: 92%
“…In a study by Varma et al 2019, IL-10 has shown a significant difference between the health, gingivitis, and periodontitis group, but the difference between health and gingivitis was higher than that between health and periodontitis. 38 When correlating both biomarkers to each other, the correlation turned out to be negative, and this correlation seems logical as IL-17 is negatively regulated by several cytokines, one of which is IL-10. 43 Published literature has reported the antagonistic roles of these two cytokines with each other as Moretti et al and Sun et al 44,45 have described a dampening effect of IL-10 on the expression of IL-17 and indicating the protective role of IL-10 in suppressing an IL-17 periodontitis trait and the upregulation of IL-17 inflammatory responses in the condition of IL-10 deficiency.…”
Section: Discussionmentioning
confidence: 97%
“…Significantly higher concentration of IL-10 in periodontitis stage I and II comparing it to health was noted; this comes in agreement with Fenol et al who found that IL-10 levels were higher in periodontitis than in health, attributing the results to the severity of the inflammatory process going on providing sufficient stimulus for a positive IL-10 response, 37 likewise, in a study by Varma et al, there was higher IL-10 levels in periodontitis stage I and II compared with health. 38 On the contrary, Tâlvan et al in 2017 39 reported higher levels of this cytokine in health despite differences in study design, samples, and settings, explained by its well-known role in maintaining the health and stability of periodontal tissues.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Periodontal disease is a multifactorial condition of inflammatory origin that results in a dysbiosis of the oral biofilm microbiome [ 1 ]. There are mainly two types of periodontal disease: gingivitis and periodontitis.…”
Section: Introductionmentioning
confidence: 99%